2004
DOI: 10.1192/bjp.184.47.s64
|View full text |Cite
|
Sign up to set email alerts
|

Diabetes mellitus and schizophrenia: Historical perspective

Abstract: BackgroundAlthough recent research has focused on the possible role of antipsychotic medications in the development of diabetes mellitus, studies conducted in the pre-neurolepticera suggest that schizophrenia itself might predispose individuals to diabetes.AimsTo test the hypothesis that diabetes mellitus is an integral part of schizophrenia.MethodHistorical literature review.ResultsMany people with severe mental illnesses, including dementia praecox, showed abnormal responses to insulin and diabetes-like gluc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
88
0
5

Year Published

2004
2004
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 151 publications
(97 citation statements)
references
References 17 publications
4
88
0
5
Order By: Relevance
“…The association between diabetes mellitus and schizophrenia has been recognized for over a century [24]. The recent literature is relatively consistent in showing a prevalence rate of diabetes of about 15% in patients with schizophrenia or an increased risk of two to threefold as compared to the general population [17].…”
Section: Psychiatric Disorders and Diabetesmentioning
confidence: 99%
See 1 more Smart Citation
“…The association between diabetes mellitus and schizophrenia has been recognized for over a century [24]. The recent literature is relatively consistent in showing a prevalence rate of diabetes of about 15% in patients with schizophrenia or an increased risk of two to threefold as compared to the general population [17].…”
Section: Psychiatric Disorders and Diabetesmentioning
confidence: 99%
“…The first reports of a link between antipsychotic medication and diabetes were made in the 1950s [24]. During the 1960s, there was a general acceptance that antipsychotic drugs could cause diabetes and the term "phenothiazine diabetes" was introduced.…”
Section: Antipsychotics and Glucose Disturbancesmentioning
confidence: 99%
“…A link between metabolic abnormalities (i.e., high blood glucose and abnormal glucose tolerance) and psychotic illness was recognized in the pre-antipsychotic era (reviewed by Kohen, 2004). Some (Ryan et al, 2003) but not all (Arranz et al, 2004, Zhang et al, 2004a more recent studies have confirmed this finding.…”
Section: Introductionmentioning
confidence: 97%
“…Besides negative psychosocial impacts (distorted selfesteem and societal stigmatization) and medications noncompliance, schizophrenics appear to be particularly susceptible to the detrimental medical sequelae of obesity such as the 'Metabolic Syndrome', which is a cluster of cardiovascular risk factors, including abdominal adiposity, insulin resistance, impaired, glucose tolerance, dyslipidemia, and hypertension (McKee et al, 1986;Mukherjee et al, 1996;Brown et al, 2000;Haupt and Newcomer, 2002;Ryan and Thakore, 2002;Ryan et al, 2003;Holt et al, 2004;Kohen, 2004;Marder et al, 2004;Lieberman et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, high rates of obesity and type II diabetes mellitus, observed in drug-naive/free patients (Mukherjee et al, 1996;Allison et al, 1999a;Thakore et al, 2002;Ryan et al, 2003Ryan et al, , 2004 before Kohen, 2004) and after the advent of antipsychotics and in nonschizophrenic blood relatives (Dynes, 1969;Mukherjee et al, 1989;Cheta et al, 1990;Martins et al, 2001;Lamberti et al, 2004), were potentially attributed to genetic factors (Stone et al, 2004), illness neurobiology (Thakore, 2005) and to unhealthy lifestyle (Brown et al, 1999). The interpretability of the preneuroleptic era data (reviewed in Kohen, 2004) is, however, limited by flaws in epidemiological methodology including lack of evaluation of and adjustments for adiposity, lifestyle, and anthropometric measures together with inconsistent diagnostic criteria for schizophrenia and glucose/insulin abnormalities Newcomer, 2005).Seeking to tackle serious methodological limitations of the early research, Thakore et al (2002) applied a wellvalidated technique of computed tomography (Mayo-Smith et al, 1989) to directly measure abdominal adiposity in a sample of drug-naive/free schizophrenic patients and ageand sex-matched healthy controls. They found that schizophrenic patients had higher body mass index (BMI) and over three times more abdominal fat , accumulation of which poses even greater cardiovascular/ diabetes risks than overall obesity .…”
mentioning
confidence: 99%